Tsunami event in Flores: literature review - Khusnani, Azmi; Jufriansah, Adi; Thalo, Ota Welly Jenni (Universitas Sebelas Maret, 2023)
The Flores Sea has experienced devastating earthquakes with magnitudes >7 over the past 30 decades. It can trigger a tsunami and provide important theoretical, experimental, and field information. The seismicity study stated that the island of Flores had experienced tsunamis during the pre-instrumental period (1815, 1818, 1820, and 1836) and the pre-instrumental period in 1992. This study discusses the development of tsunami research in Flores using a literature review approach. The data source comes from the Scopus database, with data analysis using VOSviewer. The search results obtained a total of 22 documents, with the result that the 1992 Flores earthquake became the main research topic and the beginning of the era of modern tsunami science.